Answer:
I hope this helps
Step-by-step explanation:
Simplifying
3x + -1x + -5 = 2(x + 2) + -9
Reorder the terms:
-5 + 3x + -1x = 2(x + 2) + -9
Combine like terms: 3x + -1x = 2x
-5 + 2x = 2(x + 2) + -9
Reorder the terms:
-5 + 2x = 2(2 + x) + -9
-5 + 2x = (2 * 2 + x * 2) + -9
-5 + 2x = (4 + 2x) + -9
Reorder the terms:
-5 + 2x = 4 + -9 + 2x
Combine like terms: 4 + -9 = -5
-5 + 2x = -5 + 2x
Add '5' to each side of the equation.
-5 + 5 + 2x = -5 + 5 + 2x
Combine like terms: -5 + 5 = 0
0 + 2x = -5 + 5 + 2x
2x = -5 + 5 + 2x
Combine like terms: -5 + 5 = 0
2x = 0 + 2x
2x = 2x
Add '-2x' to each side of the equation.
2x + -2x = 2x + -2x
Combine like terms: 2x + -2x = 0
0 = 2x + -2x
Combine like terms: 2x + -2x = 0
0 = 0
Solving
0 = 0
Couldn't find a variable to solve for.
This equation is an identity, all real numbers are solutions.